Efficacy of azimsulfuron against complex weed flora in transplanted rice (Oryza sativa) under rainfed shallow lowland - SAHA, SANJOY; MUNDA, SUSHMITA; ADAK, TOTAN (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted during the wet seasons of 2010 and 2011 at ICAR-National Rice Research Institute, Cuttack to study the efficacy of azimsulfuron for controlling broad spectrum of weeds in transplanted rice (Oryza sativa L.) field under rainfed shallow lowland. The present study consisted of 10 treatments which includes seven doses of azimsulfuron, viz. 12.5, 17.5, 22.5, 27.5, 30.0, 35.0 and 40 g/ha each with 0.2% surfactant along with recommended herbicide, pretilachlor at 625 g/ ha, weed-free and weedy as check. Yield attributes of rice were significantly (P<0.05) affected by weed control treatments. The highest grain yield (5.72 tonnes/ha) and N-use efficiency (57.2) were obtained in weed free check, realizing 76% increase in grain yield of rice over weedy check. Azimsulfuron at 35 and 40 g/ha applied 18 days after transplanting was found to be very effective (weed control efficiency 92.8 and 95.5%, respectively) in controlling the complex weed flora and produced comparable grain yield with weed-free check. There was more than 45% reduction in the grain yield of rice due to competition with weeds in weedy plots. The negative effect of weed competition in weedy check plot was reflected in significant reduction in crop growth rate (4.66 g/m2/day) and total biomass of rice (6.89 tonnes/ha).